Dietary Intake of Marine Polyunsaturated n-3 Fatty Acids and Risk of Recurrent Venous Thromboembolism - Isaksen, Trond; Evensen, Line H.; Brækkan, Sigrid K.; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2019)
Background Limited knowledge exists on the association between intake of long-chained n-3 polyunsaturated fatty acids (n-3 PUFAs) and risk of recurrence and all-cause mortality in patients with venous thromboembolism (VTE).Objectives This article investigates whether intake of marine n-3 PUFAs was associated with risk of recurrence and mortality in patients with incident VTE.Methods A total of 595 patients with incident VTE and available data on n-3 PUFA intake were derived from the Tromsø Study surveys 4 (1994–1995) and 6 (2007–2008). Weekly intake of n-3 PUFAs was categorized as low, medium, and high based on tertiles. Recurrent VTEs and all-cause mortality were registered up to December 31, 2016. Hazard ratios (HRs) were calculated using Cox regression models with the low intake category as reference.Results There were 98 recurrent VTEs and 227 deaths during follow-up. Overall, we found no association between intake of n-3 PUFAs and risk of recurrent VTE. However, inverse associations were found for high intakes in patients with unprovoked VTE (HR 0.45, 95% confidence interval [CI]: 0.20–1.01), cancer-free patients (HR 0.51, 95% CI: 0.27–0.95), and deep vein thrombosis (DVT) patients (HR 0.49, 95% CI: 0.24–0.97). The inverse associations were more evident when follow-up was restricted to the time after discontinuation of anticoagulant therapy. No association was observed between intake of n-3 PUFAs and mortality after incident VTE.Conclusion A high dietary intake of marine n-3 PUFAs was associated with lower risk of recurrent VTE after unprovoked index events, DVT, and in cancer-free patients.
Keywords: diet; omega-3 fatty acids; recurrence; risk factors; venous thromboembolism